2022
DOI: 10.3389/fmed.2022.858219
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Pediatric Hepatic Rhabdomyosarcoma With Maximum Lifetime

Abstract: Primary intrahepatic rhabdomyosarcoma is an extremely rare malignant tumor. Here, we describe a case of embryonal rhabdomyosarcoma of the liver in a 7-year-old boy without any symptoms. Serologically, the patient showed abnormal levels of serum tumor markers and liver function. Imaging revealed a large mass in the left lobe of the liver and no lesions elsewhere. At first, the patient was misdiagnosed by percutaneous liver biopsy as having clear cell sarcoma. However, the final diagnosis was established to be h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The Pleomorphic subtype is the most common one in advanced age groups, while the Alveolar and Embryonal subtypes occurred more in pediatric and teenage groups. [ 6 ] Only 7 cases of pleomorphic hepatic RMS have been reported and our case is the 8th one. There are only 22 cases of hepatic RMS presented in adults, and our case is the 23rd [ 2 , 6 , 7 ] ( Table.…”
Section: Discussionmentioning
confidence: 93%
“…The Pleomorphic subtype is the most common one in advanced age groups, while the Alveolar and Embryonal subtypes occurred more in pediatric and teenage groups. [ 6 ] Only 7 cases of pleomorphic hepatic RMS have been reported and our case is the 8th one. There are only 22 cases of hepatic RMS presented in adults, and our case is the 23rd [ 2 , 6 , 7 ] ( Table.…”
Section: Discussionmentioning
confidence: 93%
“…We could not make an objective assessment of the OS time even though the significant tumoral decrease was an encouraging result. For many authors in literature, tumoral prognosis is severe [18][19][20]. Some authors suggested that most patients are stratified into high-, intermediate-, and lowrisk groups based on tumor size, tumor invasiveness, nodal status, primary tumor site, and pathological and molecular parameters (PAX-fusion status) [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that most patients are stratified into high-, intermediate-, and lowrisk groups based on tumor size, tumor invasiveness, nodal status, primary tumor site, and pathological and molecular parameters (PAX-fusion status) [18,19]. In other words, prognosis for RMS depends on primary tumor site, age, completeness of resection, presence and number of metastatic sites, histology, and biology of the tumor cells [18][19][20]. In addition, the overall cure rates have improved significantly thanks to the multimodal therapies, including surgery, radiotherapy, and chemotherapy (with various combinations of vincristine, actinomycin D, cyclophosphamide, etoposide, irinotecan, or ifosfamide).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longest surviving case of hepatic RMS was the only one in literature to have received multimodality treatment. (9) Multi-modality management with surgery, radiation therapy, and chemotherapy may be a key factor affecting survival rate. (1)…”
Section: Discussionmentioning
confidence: 99%